Breksi Cliff Tourism Rising From the Impact of the Pandemic - Ferryal Abadi; Amo Sugiharto; Ria Saulina Panjaitan (Eduvest - Journal of Universal Studies, 2024)
The purpose of this study is to identify and analyze the impact of Covid-19 on Breksi Cliff Tourism. Breksi Cliff Tourism is managed by a Village-Owned Enterprise ( BUMDes) in Sambirejo Village, Prambanan District and Breksi Cliff Manager Lowo Ijo is a work unit of BUMDes. This study uses the perspective of the Balanced Scorecard (BSC), namely from a financial perspective, customer perspective, internal business process perspective, learning and growth perspective. to see the impact of Breksi Cliff Tourism. The impact on the internal organization itself as well as the economic impact on the surrounding community which has become a source of income. This study uses qualitative research methods in order to dig up more information from sources about the impact of Covid-19. The informants in this study are Breksi Cliff Tourism Managers, employees of Breksi Cliff Tourism Managers, non-employee workers and the community around Breksi Cliff Tourism. It is hoped that this research will produce a solution for Tebing Breksi Tourism Managers in dealing with the crisis caused by the Covid-19 Pandemic and can recover quickly.